Desenvolvimento de um Sistema para Pecuária de Precisão Capaz de Coletar, Armazenar e Analisar Variações das Condições Superficiais do Solo Empregando Redes de Sensores Sem Fio - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Wireless Sensor Networks (WSN) has many applications ranging from fire detection in difficult access areas to the monitoring of smart houses. Particularly, presents itself as a potential solution to the data collection of temperature, humidity and brightness over a rural area of the Pampa biome, aiming animal comfort. In this context, this paper presents the development process of a system composed of hardware and software capable of monitoring an area of the Pampa Biome using an WSN based on ZigBee / 802.15.4 protocol, specifically the sensors XBee ZB L / T / H (XS-Z16-CB2R), with which preliminary tests are developed to verify the feasibility of using these sensors according to specific application requirements: accuracy and sampling frequency of the measured data, range and battery life. Experimental evaluation includes tests (i) to define the input voltage range that supports sensor operation, (ii) to compare data measured from sensor nodes with instruments calibrated in partially controlled conditions but subjected to multipath effects, (iii) to investigate different topologies in which these sensors can operate to expand the coverage area of the network, and (iv) to demonstrate the effectiveness of the client- server application developed to gather data sent from sensor nodes and periodically transmit it to the remote server responsible for the long-term storage. Results suggest the viability of the proposed solution for collecting data over an area of native grassland in which hypothetically the effect of multipath will be further reduced. Moreover, results from the use of such kind of sensors to collect data during a given period of time in an outdoor WSN simulation are presented to confirm the effectiveness of the proposal in an external environment.
Keywords: RSSF; Pecuária de Precisão; Sensores XBee; Protocolo ZigBee; WSN; Precision livestock; XBee sensors; ZigBee protocol; CNPQ::ENGENHARIAS